ENHANCING COMMUNITY AWARENESS ON CHILDHOOD DIARRHEA PREVENTION THROUGH EDUCATIONAL PROGRAMS AND HANDWASHING DEMONSTRATIONS - Hengki Frengki Manullang; Fithri Handayanni Lubis; Herawati Br Bukit; Monika Nina Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Diarrhea remains a major health issue among children, particularly in developing countries, contributing significantly to morbidity and mortality in children under five years of age. High incidence is often associated with poor sanitation, inadequate hygiene practices, and limited caregiver knowledge regarding prevention. This community service program aimed to enhance parental and caregiver awareness of childhood diarrhea prevention through interactive education and handwashing demonstrations in the working area of Puskesmas Deli Tua. The program was conducted on Saturday, January 7, 2026, involving 55 participants who were parents or caregivers of children aged 1–5 years. The intervention comprised health education on the causes and risk factors of diarrhea, the importance of sanitation, and hygienic practices, coupled with practical demonstrations of handwashing based on the WHO seven-step method. Visual materials, including posters, leaflets, and educational stickers, were used to reinforce participants’ understanding. Data collection involved pre- and post-intervention assessments of knowledge and attitudes, as well as observation of handwashing practices. Results indicated a significant improvement in participants’ knowledge, attitudes, and skills; nearly all participants performed correct handwashing techniques and expressed commitment to consistently apply hygiene practices at home. These findings demonstrate that participatory educational approaches reinforced with practical demonstrations and visual aids are effective in promoting hygienic behavior and preventing childhood diarrhea. This program can serve as a model for community-based interventions aimed at improving child health outcomes in other areas with similar social and demographic characteristics.